EFFECT OF FINANCIAL STRESS ON BURNOUT AMONG FARMERS IN ENUGU STATE, NIGERIA - N, Egbo Beatrice (Journal of Advance Research in Food, Agriculture and Environmental Science (ISSN 2208-2417), 2022)
The present-day dwindling economic conditions have affected every aspect of human functionality. Several authors have underscored the pattern and prospects of financial stress accompanying the current economic realities in Nigeria. However, little is known about the role of financial burden in farmer's fatigue. The present study examined financial stress as a scarcely explored variable that could predict burnout in a sample of farmers in Enugu state, Nigeria. One hundred and ninety-eight farmers were recruited for the study. They completed a self-report measure of the Maslach Burnout Inventory (MBI) developed by Maslach et al. (2018) and the Financial Stress Scale (FSS) developed by Northern et al. (2010). Data were analyzed using the statistical package for social sciences SPSS, Version 23. The result of a linear regression indicated that financial stress statistically predicted farmers' burnout F (1,196), 21.36 P< .05 with an R2 of 118. In particular, the result revealed that financial stress accounted for about 11.8% of the variation in farmers' burnout. The finding offers valuable data to the psychologists and counselors who might be interested in improving farmers' resilience.